Between Policy Idealism and Coastal Reality: A Qualitative Portrait of the Cities Without Slums Program Implementation in Lappa Village - Almasyah Pratama; Lukman Dahlan (Phinisi Applied Accounting Journal, 2026)
This study evaluates the implementation and sustainability prospects of the "Kota Tanpa Kumuh" (KOTAKU) program in Lappa Village, Sinjai Regency, a prominent coastal fishing community facing complex slum vulnerabilities. Employing a qualitative-descriptive design, the analysis utilizes Merilee S. Grindle’s policy implementation framework integrated with sustainable urban development dimensions (SDG 11). Data were gathered through field observations, institutional secondary baselines, and semi-structured interviews with key stakeholders.The findings indicate that the program successfully reduced the slum area from 30 hectares in 2016 to 22.59 hectares in 2019, lowering the technical slum score from 38 to 27 ("mild slum"). While the content of the policy effectively delivered infrastructure upgrades, the context of implementation encountered sociopolitical frictions, such as localized interest conflicts and budget restructuring. In terms of sustainability, the social dimension demonstrated high resilience, driven by structural inclusivity and the traditional Bugis cooperative value of mappideceng. Conversely, ecological sustainability remains vulnerable because the conventional drainage interventions fail to mitigate seasonal tidal floods (rob). Furthermore, economic sustainability is highly compromised due to a complete lack of post-project financial maintenance frameworks and structured livelihood empowerment for low-income households. Ultimately, this research highlights that local institutional capacity (BKM) serves as a fundamental, independent pillar essential for ensuring long-term self-reliance in slum alleviation